Cataloguing Ethics: a world overview and a focus on Portugal: literature review - Pena, Rita Anjos (Páginas a&b: arquivos e bibliotecas, 2022)
This literary review was written with the intent of exposing what is cataloguing ethics and how it should influence the cataloguer's work. What do cataloguers understand by cataloguing ethics, what codes of ethics exist now and how they came into existence. It goes into ethical problems and proposed solutions as well as world differences in information accessibility and cataloguing standards, with a focus on what is the Portuguese reality in terms of cataloguing codes of ethics.